Active and reactive control method of flexible ring network device - HAN MINXIAO; ZHAO GUOPENG; LI YUN; HUANG RENLAO; HE YANLIANG (2016)
The invention belongs to the field of application of a power electronic device in distribution networks, and particularly relates to an active and reactive control method of a flexible ring network device. According to the invention, three or four distribution networks are connected so as to form a ring network for a three-terminal or four-terminal flexible ring network device, and operation strategies of active power and reactive power of the flexible ring network device in the distribution networks are defined in a safe region for power scheduling. According to the invention, basic voltage-current double loop control is adopted, and analysis and explanation are carried out on distribution of active power and reactive power of the flexible ring network device under different conditions. The proportion between active power and reactive power is distributed according to the device capacity, and active power exchange between the distribution networks and reactive control in each distribution network are realize